Ionic Liquid@ HT- Clay Combination for Baylis -Hillman Reaction and Lactone Ceramide Analog Synthesis - Srivastava, Vivek (Letters in Organic Chemistry, 2024)
This study investigates the use of ionic liquids (ILs) immobilized on HT-clay as catalysts for the Baylis-Hillman reaction. The catalytic system comprised three different types of ILs ([HIM]Im, [BIM]Im, [EIM]Im) and exhibited high reactivity, and the B-H products were obtained in good yield, which is superior to previously reported catalytic systems, whether they were heterogeneous or homogeneous. The HT-clay immobilized with ILs also allowed for easy recovery from the reaction mass and could be recycled for up to 7 consecutive runs with only a slight decrease in activity. Moreover, the scope of our catalytic system was extended to synthesize biologically active lactone ceramide analogs using the Baylis-Hillman reaction at room temperature with (S-) Garner aldehyde and methyl acrylate. The synthesis was successful, and we obtained good yields of the desired products, highlighting the versatility of the ionic liquid immobilized HT-clay catalytic system. This study demonstrates the potential of ionic liquid immobilized HT-clay as a promising catalyst for various organic reactions. Our findings emphasize the importance of developing efficient and environmentally friendly methods for synthesizing valuable organic compounds. The results obtained from this study provide a significant contribution to the ongoing research in the field of catalysis and will be useful for developing new approaches to the synthesis of complex organic molecules.
Keywords: Ionic liquids